Dosimetric and kinetic characteristics of watch glass sample. (February 2016) - Aydaş, Canan; Yüce, Ülkü R.; Engin, Birol; Polymeris, George S.
Abstract: This paper reports the Electron Spin Resonance (ESR) and Thermoluminescence (TL) dosimetric and kinetic characteristics of commercial watch glass. Both of the ESR and TL response of the watch glass sample yielded linear behavior in the 0.5–135 Gy gamma dose range. ESR dosimetric properties of watch glass sample like dose-rate dependence, signal reproducibility and fading behavior have also been studied in detail. Kinetic behavior and activation energy of the radiation induced free radicals responsible from the ESR spectra of watch glass sample were determined. The TL kinetic parameters such as activation energy (E), frequency factor (s), order of kinetics (b) were also calculated by applying the methods of initial rise (IR), isothermal decay (ID), variable heating rate (VHR) and de-convolution. Highlights: Linear dose response of watch glass sample are observed in the 0.5–135 Gy range. Kinetic parameters were determined applying various methods of analysis. ESR and TL dosimetric characteristics of watch glass samples were investigated. Watch glass samples can be used as alternative accident dosimeter using ESR and TL.